1997
DOI: 10.1097/00004836-199710000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterolosis Is Not Associated With High Cholesterol Levels in Patients With and Without Gallstone Disease

Abstract: High levels of cholesterol have been associated with certain gallbladder disorders such as cholesterolosis and gallstone disease. Furthermore, obesity is considered the main risk factor for cholesterol gallstone disease. We investigated the incidence of cholesterolosis in patients with and patients without gallbladder stones (GS). We reviewed the clinical records of patients with gallstone disease and other gallbladder disorders who had consecutive cholecystectomy during a 5-year period. We recorded demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
2
7
0
3
Order By: Relevance
“… 3 Mendez-Sanchez et al even suggested cholesterol polyps are not associated high serum cholesterol level. 6 Notably, our results were consistent with the literature to demonstrate hyperlipidemia was only found in 24.6% of our GP patients (Table 1 ). The possible explanation for the association between increased risk of stroke and cholesterol polyps observed in the patients with normal serum cholesterollevelisACAT2 contributes proatherosclerotic effect by facilitating cholesterol absorption in the liver and intestines to incorporate cholesteryl esters (CEs) into apoB-containing lipoproteins, which mainly accumulate in the intima of arteries, with disproportionally less increased serum cholesterol level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 3 Mendez-Sanchez et al even suggested cholesterol polyps are not associated high serum cholesterol level. 6 Notably, our results were consistent with the literature to demonstrate hyperlipidemia was only found in 24.6% of our GP patients (Table 1 ). The possible explanation for the association between increased risk of stroke and cholesterol polyps observed in the patients with normal serum cholesterollevelisACAT2 contributes proatherosclerotic effect by facilitating cholesterol absorption in the liver and intestines to incorporate cholesteryl esters (CEs) into apoB-containing lipoproteins, which mainly accumulate in the intima of arteries, with disproportionally less increased serum cholesterol level.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the stasis of venous and lymphatic systems disturbs cholesterol absorption and secretion mechanisms of the gallbladder mucosa to result in the development of cholesterol polyps. 6 – 10 Nevertheless, adenomyomatosis and inflammatory polyps are related to chronic inflammation with bile sludges or gallstones. The risk factors for GPs remain inconclusive, although the male sex, glucose intolerance, obesity, and several components of metabolic syndrome are possibly related to GP development.…”
Section: Introductionmentioning
confidence: 99%
“…In this study cholesterolosis was seen in 34 of 56 (61%) patients and we did not find any correlation between serum LDL, HDL, triglyceride and cholesterol levels and cholesterolosis. Similar to our findings, Mendez‐Sanchez et al 16 reported that cholesterolosis is not associated with high cholesterol levels in patients with and without gallstone disease. Also, Watanabe et al 13 suggested that cholesterol ester synthesis of gallbladder mucosa might play an etiological role in the development of cholesterolosis.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to gallstones, our study showed that GP had the predilection of male gender. Estrogen may protect from the development of GP since it can impair the esterification of cholesterol by reducing the activity of both hepatic and intestinal acyl-CoA: cholesterol acyltransferase 2 (ACAT2), an enzyme facilitating the pinocytosis of cholesterol and papillary hyperplasia in the gallbladder mucosa (28).…”
Section: Discussionmentioning
confidence: 99%